Medieval Literacy and Textuality in Middle High German Reading and Writing in Albrecht's Jüngerer Titurel - Volfing, A.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2007)
This study addresses the topics of literacy and texuality in order to develop a new line of interpretation for a landmark of Middle High German literature. Albrecht's Der jüngere Titurel is an intellectually ambitious narrative written ca. 1270 as a prequel and sequel to the more famous Arthurian texts by Wolfram von Eschenbach.
Keywords: Literature, Medieval; Classical literature; Medieval Literature; Classical and Antique Literature